2014
DOI: 10.1073/pnas.1418545112
|View full text |Cite
|
Sign up to set email alerts
|

Soil surface acidity plays a determining role in the atmospheric-terrestrial exchange of nitrous acid

Abstract: Nitrous acid (HONO) is an important hydroxyl (OH) radical source that is formed on both ground and aerosol surfaces in the wellmixed boundary layer. Recent studies report the release of HONO from nonacidic soils, although it is unclear how soil that is more basic than the pK a of HONO (∼3) is capable of protonating soil nitrite to serve as an atmospheric HONO source. Here, we used a coated-wall flow tube and chemical ionization mass spectrometry (CIMS) to study the pH dependence of HONO uptake onto agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 71 publications
4
94
0
Order By: Relevance
“…In these diffusion-limited environments, the accumulation of microbial metabolic products (e.g., NH 4 + , NO 2 − , and NO 3 − ) may maintain a flux of NO even as soils dry (23,26,32,37). NO 2 − , in particular, is chemically reactive (38) and, in dry soils, may be less likely to be oxidized by nitrifiers but may still chemodenitrify (10,29,39). At our site, NO 2 − concentrations averaged 0.6 μg NO 2 − -N g −1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these diffusion-limited environments, the accumulation of microbial metabolic products (e.g., NH 4 + , NO 2 − , and NO 3 − ) may maintain a flux of NO even as soils dry (23,26,32,37). NO 2 − , in particular, is chemically reactive (38) and, in dry soils, may be less likely to be oxidized by nitrifiers but may still chemodenitrify (10,29,39). At our site, NO 2 − concentrations averaged 0.6 μg NO 2 − -N g −1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Chemodenitrification encompasses all of the abiotic nonenzymatic processes that produce NO, including chemical decomposition of nitrous acid as well as reactions between N substrates with reduced metals and humic substances (9)(10)(11). The biological processes that produce NO, however, are numerous [e.g., nitrification, denitrification, nitrifier denitrification, dissimilatory nitrate reduction to ammonium, and anaerobic ammonium oxidation (9)], but nitrification is generally considered the dominant driver of NO emissions under aerobic conditions (12).…”
mentioning
confidence: 99%
“…These results stimulated laboratory investigations on potential HONO precursors from which the most frequently discussed mechanisms are (i) the photosensitized reduction of nitrogen dioxide (NO 2 ) by organic material, e.g. humic acids (George et al, 2005;Stemmler et al, 2006;2007, Sosedova et al, 2011Han et al, 2016), (ii) the photolysis of adsorbed nitric acid (Zhou et al, , 2011Laufs and Kleffmann, 2016), (iii) biogenic production of nitrite in soil (Su et al, 2011;Ostwald et al, 2013;Maljanen et al, 2013;Oswald et al, 2015;Scharko et al, 2015;Weber, 2015) and (iv) release of adsorbed HONO from soil surfaces after deposition of strong acids (VandenBoer et al, 2013(VandenBoer et al, , 2014(VandenBoer et al, , 2015Donaldson et al, 2014). Another discussed source, the reaction of excited gaseous NO 2 with water (Li et al, 2008), is of minor importance as demonstrated by laboratory (Crowley and Carl, 1997;Carr et al, 2009;Amedro et al, 2011) and modelling studies (Sörgel et al, 2011b;Czader et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…However, it has been shown that the nature of the surface, and particularly surface charge, plays an important role in the uptake and release of HONO from soils. 232 For example, as shown in Fig. 8b, soil surface components such as aluminum and iron oxides/hydroxides are present in a number of different forms such as MO À , M-OH and MOH 2 + (M ¼ metal) which interact with oxides of nitrogen, changing the pH at which HONO is released to more basic conditions compared to pure water by as much as several pH units.…”
Section: -218mentioning
confidence: 99%